2021
DOI: 10.1017/jog.2020.108
|View full text |Cite
|
Sign up to set email alerts
|

Geodetic mass balance of Abramov Glacier from 1975 to 2015

Abstract: Multi-decadal mass loss estimates are available for few glaciers of Central Asia. On Abramov Glacier (Pamir-Alay, Kyrgyzstan), comprehensive long-term glaciological measurements have been carried out from 1968 to 1999 and re-initiated in 2011. A climatological interpretation of this benchmark glacier in Central Asia requires bridging the gap between historical and renewed measurements. This is achieved here by computing the geodetic mass balance from 1975 to 2015 using previously unreleased Soviet aerial image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 69 publications
(107 reference statements)
2
17
0
Order By: Relevance
“…Given the trend towards increased net accumulation rates at ~4400 m a.s.l., the slight surface lowering since the 1980s detected based on legacy pictures is not self-explanatory. The observed lowering agrees with the geodetic elevation changes (1975–2015) for this part of the glacier determined by Denzinger and others (in press). The very moderate surface lowering in the accumulation area contrasts sharply with the observed surface lowering of up to 151.3 ± 5.5 m on the glacier tongue (Denzinger and others, in press).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Given the trend towards increased net accumulation rates at ~4400 m a.s.l., the slight surface lowering since the 1980s detected based on legacy pictures is not self-explanatory. The observed lowering agrees with the geodetic elevation changes (1975–2015) for this part of the glacier determined by Denzinger and others (in press). The very moderate surface lowering in the accumulation area contrasts sharply with the observed surface lowering of up to 151.3 ± 5.5 m on the glacier tongue (Denzinger and others, in press).…”
Section: Discussionsupporting
confidence: 90%
“…The observed lowering agrees with the geodetic elevation changes (1975–2015) for this part of the glacier determined by Denzinger and others (in press). The very moderate surface lowering in the accumulation area contrasts sharply with the observed surface lowering of up to 151.3 ± 5.5 m on the glacier tongue (Denzinger and others, in press). The slight surface lowering in the accumulation area may be related to glacier dynamics and/or may have happened in the 1980s or during the period without available observations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Their model is based on a simplified energy-balance approach by Oerlemans (2001). Denzinger et al (2021) computed the geodetic mass balance based on aerial imagery from 1975 and satellite stereo pairs from 2015. Both studies found an overall negative mass balance.…”
Section: Abramov Glaciermentioning
confidence: 99%